2020
DOI: 10.3390/metabo10120481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging, Long-Term and Lifelong Exercise on the Urinary Metabolic Footprint of Rats

Abstract: Life expectancy has risen in the past decades, resulting in an increase in the number of aged individuals. Exercise remains one of the most cost-effective treatments against disease and the physical consequences of aging. The purpose of this research was to investigate the effects of aging, long-term and lifelong exercise on the rat urinary metabolome. Thirty-six male Wistar rats were divided into four equal groups: exercise from 3 to 12 months of age (A), lifelong exercise from 3 to 21 months of age (B), no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Previous work of our team on specimens from the same in vivo study revealed aging as the most profound variable compared to exercise on the blood, urine, and fecal sample metabolome, in both sexes. , Urine metabolites that belong to amino acids, pyrimidines, and their derivatives were significantly affected by the exercise in both sexes, while amines, alcohols, polyols, alpha hydroxy acids, and carbohydrates were only affected in female rats. , Blood metabolic profiling of exercise training rats demonstrated amino acids, carbohydrates, carboxylic acids, and amines to be subjected to an exercise effect. , The fecal sample metabolome alterations triggered by exercise training were of paramount importance, since compounds from both purine and pyrimidine derivatives, carbohydrate and fatty acid conjugates, amines, amino acids, alcohols, and polyols were significantly changed. Fecal samples were proven to be a more sensitive biospecimen capturing the endogenous response under the exercise training stimulus …”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous work of our team on specimens from the same in vivo study revealed aging as the most profound variable compared to exercise on the blood, urine, and fecal sample metabolome, in both sexes. , Urine metabolites that belong to amino acids, pyrimidines, and their derivatives were significantly affected by the exercise in both sexes, while amines, alcohols, polyols, alpha hydroxy acids, and carbohydrates were only affected in female rats. , Blood metabolic profiling of exercise training rats demonstrated amino acids, carbohydrates, carboxylic acids, and amines to be subjected to an exercise effect. , The fecal sample metabolome alterations triggered by exercise training were of paramount importance, since compounds from both purine and pyrimidine derivatives, carbohydrate and fatty acid conjugates, amines, amino acids, alcohols, and polyols were significantly changed. Fecal samples were proven to be a more sensitive biospecimen capturing the endogenous response under the exercise training stimulus …”
Section: Discussionmentioning
confidence: 88%
“…5,23−25 Urine metabolites that belong to amino acids, pyrimidines, and their derivatives were significantly affected by the exercise in both sexes, while amines, alcohols, polyols, alpha hydroxy acids, and carbohydrates were only affected in female rats. 5,25 Blood metabolic profiling of exercise training rats demonstrated amino acids, carbohydrates, carboxylic acids, and amines to be subjected to an exercise effect. 5,24 The fecal sample metabolome alterations triggered by exercise training were of paramount importance, since compounds from both purine and pyrimidine derivatives, carbohydrate and fatty acid conjugates, amines, amino acids, alcohols, and polyols were significantly changed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the changes in the metabolome can be different regarding the modality of exercise intervention. It was previously established that following a 2week sprint interval training in obese men, some metabolic parameters changed significantly immediately after exercise compared to baseline, but these changes were not significant anymore 72 h following the intervention (Tzimou et al, 2020). When comparing the durations, their intervention is considered short-term whereas our intervention is considered long-term (12 weeks).…”
Section: Metabolome Adaptationsmentioning
confidence: 99%
“…Additionally, a recent review reported that metabolite levels can be influenced by nutrition (18). Aging and exercise affect the rat urinary metabolome, and exercise attenuated the consequences of aging (19).…”
Section: Introductionmentioning
confidence: 99%